2021
DOI: 10.3389/fped.2021.649358
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Clinical Features and Prognostic Factors of Pediatric SARS-CoV-2 Infection: Results From an Italian Multicenter Study

Abstract: Background: Many aspects of SARS-CoV-2 infection in children and adolescents remain unclear and optimal treatment is debated. The objective of our study was to investigate epidemiological, clinical and therapeutic characteristics of pediatric SARS-CoV-2 infection, focusing on risk factors for complicated and critical disease.Methods: The present multicenter Italian study was promoted by the Italian Society of Pediatric Infectious Diseases, involving both pediatric hospitals and general pediatricians/family doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 25 publications
3
44
1
2
Order By: Relevance
“… 5 , 6 Evidence from a large multicenter study in Italy showed that diarrhea occurs in about 15% of children with COVID-19, with a more frequent presentation in infancy, and vomiting (10%) or abdominal pain (8%) have a higher frequency in school-aged children. 7 …”
Section: Introductionmentioning
confidence: 55%
“… 5 , 6 Evidence from a large multicenter study in Italy showed that diarrhea occurs in about 15% of children with COVID-19, with a more frequent presentation in infancy, and vomiting (10%) or abdominal pain (8%) have a higher frequency in school-aged children. 7 …”
Section: Introductionmentioning
confidence: 55%
“…A substantial number of patients with the novel coronavirus disease 2019 (COVID-19) experience gastrointestinal (GI) symptoms 1 3 . Prevalence estimates vary between studies, with higher rates noted among children 4 , but up to 39.6% of all patients with COVID-19 are believed to experience associated diarrhea 5 . The prognostic implications of diarrhea in patients with COVID-19 requires further investigation, but there is increasing evidence of correlations with both disease severity and survival 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In Italy, paediatric SARS‐CoV‐2 infection presented in most cases with few symptoms or even in asymptomatic form, although nearly 20% of children enrolled in a nationwide registry developed complications, especially in the presence of comorbidities. 1 However, in some children and adolescents, SARS‐CoV‐2 infection was associated with the so‐called multisystemic inflammatory disease (MIS‐C), which required hospitalisation and therapies. MIS‐C is thought to be caused by a postinfectious inflammatory process and manifests clinically with signs and symptom like those of Kawasaki disease (KD) but is also marked by clinical manifestations unusual in KD, particularly gastrointestinal complaints and myocarditis, often leading to myocardial failure and shock.…”
mentioning
confidence: 99%